A scoping review of autoethnography in nursing - Martin Salzmann-Erikson (Elsevier, 2024)
Objective: Autoethnography combines personal experiences with cultural analysis, emerging as a response to the limitations of traditional ethnography. This review aimed to explore, describe, and delineate the utilization of autoethnography by nurses published in peer-reviewed journals. Methods: A scoping review was conducted according to the Arksey and O'Malley framework. On October 12, 2023, autoethnographic studies in nursing were identified through searches of CINAHL, PubMed, PsycINFO, and Scopus. Peer-reviewed articles published in English language were retrieved. We applied no date restriction. Data were extracted on nursing, epiphany, results, style of writing, implications for nursing, and ethical considerations. Results: Twenty-six articles met the inclusion criteria. Mental health nursing, covered by nine articles, elucidated experiences of stigma, ethical dilemmas, and professional identity. Nursing education, represented by seven articles, highlighted identity struggles, systemic biases, and evolving pedagogies. Palliative care, addressed by three articles, provided insights into communication challenges and emotional complexities in end-of-life care. The remaining articles explored rehabilitation, cultural competence, and chronic pain management. A conceptual framework integrating ontological, epistemological, ethical, and practical dimensions was developed, emphasizing the interplay between personal and professional roles. Conclusions: This review underscores autoethnography's value in uncovering the cultural and ethical dimensions of nursing. This framework advocates for a reflective, culturally attuned approach to healthcare, fostering transformative changes in nursing. Further research should explore underrepresented nursing specialties to harness autoethnography's potential fully.